The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1073/pnas.0611732104
|View full text |Cite
|
Sign up to set email alerts
|

Importance of culturing primary lymphocytes at physiological oxygen levels

Abstract: Although studies with primary lymphocytes are almost always conducted in CO 2 incubators maintained at atmospheric oxygen levels (atmosO 2 ; 20%), the physiological oxygen levels (physO 2 ; 5%) that cells encounter in vivo are 2-4 times lower. We show here that culturing primary T cells at atmosO 2 significantly alters the intracellular redox state (decreases intracellular glutathione, increases oxidized intracellular glutathione), whereas culturing at physO2 maintains the intracellular redox environment (intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
143
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(156 citation statements)
references
References 37 publications
12
143
1
Order By: Relevance
“…Likewise, the nrdD mutant grew indistinguishably from SK36 under these same conditions. We have recently shown that growth of S. sanguinis sodA (superoxide dismutase) and ssaB mutants in rabbit serum under 12% O 2 , the level present in arterial blood (44), closely mimics the results of virulence studies performed in the rabbit model. 4 Neither the nrdI nor nrdHEKF mutants were recovered after 24 h of 37°C incubation under these conditions (data not shown).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Likewise, the nrdD mutant grew indistinguishably from SK36 under these same conditions. We have recently shown that growth of S. sanguinis sodA (superoxide dismutase) and ssaB mutants in rabbit serum under 12% O 2 , the level present in arterial blood (44), closely mimics the results of virulence studies performed in the rabbit model. 4 Neither the nrdI nor nrdHEKF mutants were recovered after 24 h of 37°C incubation under these conditions (data not shown).…”
Section: Discussionmentioning
confidence: 85%
“…Loss of NrdF expression was confirmed by Western blot (data not shown). As would be expected for a strain whose only remaining RNR is a class III (anaerobic) enzyme (15,43), the mutant could not be propagated in the presence of 6% O 2 , our usual microaerobic growth condition, which is also similar to dissolved O 2 concentrations in venous blood (44). Indeed, this mutant routinely failed to grow in BHI broth under an atmosphere of as little as 1% O 2 (data not shown).…”
Section: Mutagenesis Of S Sanguinis Genes Required Formentioning
confidence: 89%
“…Thus, although lymphocytes encounter fluctuations in O 2 levels in vivo, the physiological range of O 2 levels to which they are exposed is at least two to six times lower than the 20% O 2 levels maintained in standard incubators. Culturing at atmospheric O 2 levels has been shown to result in altered cell proliferation rates and other skewed T-cell responses (16,(19)(20)(21)(22)(23). Thus, because the goal of in vitro studies is generally to reveal information of in vivo significance, our studies here focus on findings with peripheral blood T cells cultured at physiological O 2 levels.…”
mentioning
confidence: 99%
“…1). However, the implied caution has largely been ignored, keeping the entrenched culture methods in use despite the rapidly growing recognition that all cell types sense and respond to even small shifts in oxygen levels (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…In the overwhelming majority of such studies today, cells are cultured in incubators that are gassed with a mixture of CO 2 and air, which maintains the internal oxygen level essentially at atmospheric oxygen (atmosO 2 ) levels (atmosO 2 , 20-21% O 2 ,). The biomedical community (or at least some portion thereof) has, of course, been aware that these oxygen levels are 2-to 4-fold greater than the oxygen levels that lymphocytes and most other cells encounter in vivo (Fig.…”
mentioning
confidence: 99%